Música, temporalidade e emoção nos bailes da saudade de Belém, Pará, Brasil - CASTRO, Fábio Fonseca de (Universidade Federal da Paraíba, 2022)
The work presents the results of ethnography carried out in the bailes da saudade (balls of nostalgia) in Belem, Para, Brazil, and seeks to discuss the artifices and dispositives for the production of temporality in the urban culture of that city. In this perspective, an attempt is made to understand the relationship between music, temporality and emotion using Heidegger's (2012) reflections on daily temporality, Derrida (1972; 1994) on the question of the “metaphysics of presence” and Schütz (1967; 2012), about the intersubjective processes that make up culture.